Spirulina and its residual biomass as alternative sustainable ingredients: impact on the rheological and nutritional features of wheat bread manufacture - Fratelli, Camilly; Nunes, Maria Cristiana; De Rosso, Veridiana Vera; Raymundo, Anabela; Braga, Anna Rafaela Cavalcante (Frontiers in Food Science and Technology, 2023)
Introduction: Following consumers’ demand for healthier alternatives, Spirulina biomass has been included as a functional ingredient in different types of food as a sustainable alternative to improve physicochemical characteristics and nutritional aspects in the diet. This study aimed to explore the use of Spirulina biomass (SB) and residual biomass (RB) obtained after C-phycocyanin (C-PC) extraction in the production of wheat bread (WB). Methods: The dough rheology, texture, color, nutritional aspects, and bioaccessibility of the different manufactured bread samples were accessed to achieve this goal. Results and Discussion: This is the first research to exploit RB. It was possible to replace 3% of wheat flour for SB or RB in bread-making; this substitution did not impact the rheological characteristics of the dough, even though the pH increased with the addition of SB or RB (5.63 and 5.70, respectively). SB and RB addition improved bread volume and enhanced the nutritional profile, increasing the antioxidant capacity (DPPH and FRAP) compared to WB. Heavy metals (Ni, Cd, and Pb) were not found in any of the samples (<0.2 mg/100 g). The in vitro protein digestibility in bread was better than in SB and RB raw materials, which indicates that bread manufacturing may contribute to improving protein digestibility. In addition, SB needs greater appreciation for sustainable food practices worldwide and in Brazilian exploration, requiring management strategies with industry and society working together. Further studies are necessary, focusing on acceptability to understand the viability of these ingredients to target consumers’ preferences.